An In Vitro Mixed Infection Model With Commensal and Pathogenic Staphylococci for the Exploration of Interspecific Interactions and Their Impacts on Skin Physiology - Kohda, Katsunori; Li, Xuan; Soga, Naoki; Nagura, Risa; Duerna, Tie; Nakajima, Saeko; Nakagawa, Ichiro; Ito, Masakazu; Ikeuchi, Akinori (Frontiers in Cellular and Infection Microbiology, 2021)
The skin microbiota has been recognized to play an integral role in the physiology and pathology of the skin. The crosstalk between skin and the resident microbes has been extensively investigated using two-dimensional (2D) and three-dimensional (3D) cell cultures in vitro; however, skin colonization by multiple species and the effects of interspecific interactions on the structure and function of skin remains to be elucidated. This study reports the establishment of a mixed infection model, incorporating both commensal (Staphylococcus epidermidis) and pathogenic (Staphylococcus aureus) bacteria, based on a 3D human epidermal model. We observed that co-infecting the 3D epidermal model with S. aureus and S. epidermidis restricted the growth of S. aureus. In addition, S. aureus induced epidermal cytotoxicity, and the release of proinflammatory cytokines was attenuated by the S. aureus-S. epidermidis mixed infection model. S. epidermidis also inhibited the invasion of the deeper epidermis by S. aureus, eliciting protective effects on the integrity of the epidermal barrier. This 3D culture-based mixed infection model would be an effective replacement for existing animal models and 2D cell culture approaches for the evaluation of diverse biotic and abiotic factors involved in maintaining skin health.